2011
DOI: 10.1016/s1413-8670(11)70224-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification and typing of Mycobacterium massiliense isolated from postsurgical infections in Brazil

Abstract: These findings suggest a common source of infection for all patients and reinforce the hypotheses of spread of M. massiliense BRA100 in Brazilian hospital surgical environment in recent years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 25 publications
1
17
1
Order By: Relevance
“…Outbreak 2 was a nationwide epidemic of surgical site infections related to laparoscopic and arthroscopic surgeries, which generated Ͼ2,000 notifications from several states to the Brazilian federal authorities between 2004 and 2008 (10,(31)(32)(33). The study of 157 isolates from the seven states that reported the most cases showed that the infections were caused by a single strain of M. abscessus subsp.…”
Section: Mycobacterial Isolatesmentioning
confidence: 99%
“…Outbreak 2 was a nationwide epidemic of surgical site infections related to laparoscopic and arthroscopic surgeries, which generated Ͼ2,000 notifications from several states to the Brazilian federal authorities between 2004 and 2008 (10,(31)(32)(33). The study of 157 isolates from the seven states that reported the most cases showed that the infections were caused by a single strain of M. abscessus subsp.…”
Section: Mycobacterial Isolatesmentioning
confidence: 99%
“…The M. abscessus complex comprises ubiquitous environmental micro-organisms that are frequently associated with hospital-acquired outbreaks and pseudo-outbreaks (Brown-Elliott & Wallace, 2002;Duarte et al, 2009;Fisher & Gloster, 2005;Monego et al, 2011;Nunes et al, 2014). The subspecies of the M. abscessus complex have undergone taxonomical nomenclature changes, previously classified as three separate subspecies: M. abscessus subsp.…”
Section: Introductionmentioning
confidence: 99%
“…bolletii strains. In addition, previous publications have confirmed that outbreak strains, whether harboring the pMAB01 plasmid or not, are fully susceptible to amikacin (AMI) (MIC ϭ 4 g/ml or 8 g/ml) (8)(9)(10).…”
mentioning
confidence: 93%